2021
DOI: 10.4049/jimmunol.2000765
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Agonist Overcomes T Cell Exhaustion Induced by Chronic Myeloid Cell IL-27 Production in a Pancreatic Cancer Preclinical Model

Abstract: Pancreatic cancer is a particularly lethal malignancy and resists immunotherapy. Here, using a preclinical pancreatic cancer murine model, we demonstrate a progressive decrease in IFNγ and Granzyme B and a concomitant increase in Tox and IL-10 in intratumoral tumor-specific T cells. Intratumoral myeloid cells produced elevated IL-27, a cytokine that correlates with poor patient outcome. Abrogating IL-27 signaling significantly decreased intratumoral Tox+ T cells and delayed tumor growth yet was not curative. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 80 publications
7
57
0
Order By: Relevance
“…When intratumorally CD8 + T cells are present they are usually exhausted and express checkpoints such as TIGIT ( 11 ), lymphocyte-activation gene 3 (LAG-3) and PD-1 ( 32 , 142 ). Recent research identified intratumoral exhausted T cells (PD-1 + Lag3 + Tox + ) as induced by myeloid cell derived IL-27 in an orthotopic model of PDA ( 143 ). Those intratumoral T cells not only produced less IFNγ and Granzyme B but also expressed more IL-10, thus contributing to immune suppression in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…When intratumorally CD8 + T cells are present they are usually exhausted and express checkpoints such as TIGIT ( 11 ), lymphocyte-activation gene 3 (LAG-3) and PD-1 ( 32 , 142 ). Recent research identified intratumoral exhausted T cells (PD-1 + Lag3 + Tox + ) as induced by myeloid cell derived IL-27 in an orthotopic model of PDA ( 143 ). Those intratumoral T cells not only produced less IFNγ and Granzyme B but also expressed more IL-10, thus contributing to immune suppression in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is largely absent on T cells infiltrating PDA. Most Lag3+Klrg1-T cells were exhausted whereas Lag3-Klrg1+ T cells were enriched intratumorally during a productive immunotherapy responses (23,64) and highly functional. Klrg1 is expressed on NK cells (65) and effector CD8 T cells during acute viral infection (66,67).…”
Section: Cd8 T Cell Exhaustion Is Driven By Persistent Tcr Signalingmentioning
confidence: 99%
“…In contrast, T cells with identical peptide specificity remained largely functional in the spleens within the same tumor-bearing animals, indicating that the tumor and/or the TME drive T cell functional loss. Tox is elevated in both functional effector splenic CD8 T cells as well as intratumoral exhausted CD8 T cells (64). Early during tumor growth, intratumoral tumor-specific T cells co-express both Tox and Granzyme B and produce cytokines following antigen encounter.…”
Section: Cd8 T Cell Exhaustion Is Driven By Persistent Tcr Signalingmentioning
confidence: 99%
See 2 more Smart Citations